Motivating Learners Through Gamification: Effective Game Elements and Key Factors - Ahmad Nizamuddin Jipli; Dr. Ahmad M. S. Elaklouk, (International Journal of Innovative Technology and Exploring Engineering (IJITEE), 2025)
Gamification, which incorporates game design principles within non-gaming environments, has garnered widespread interest in bolstering motivation and engagement across various industries and sectors. While gamification has seen extensive adoption and is projected to grow, further research is needed to explore gamification in education. This paper aims to investigate gamification use in educational contexts using the Systematic Review approach, finding practical game elements and factors contributing to students’ motivation and engagement and offering educators and researchers to develop impactful educational gamification strategies. Finally, the review identifies gaps and outlines directions for future research in this field, as it ultimately identifies various challenges and prospective research avenues within this domain.